2020
DOI: 10.3390/rs12183071
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Seasonal Deformation of Highway Overpasses Using the PS-InSAR Technique: A Case Study in Beijing Urban Area

Abstract: In urban areas, deformation of transportation infrastructures may lead to serious safety accidents. Timely and accurate monitoring of the structural deformation is critical for prevention of transportation accidents and assurance of construction quality, particularly in areas with regional land subsidence, such as the city of Beijing. In this study, we proposed a method for the detection of seasonal deformation of highway overpasses using the integration of persistent scatterers Interferometric Synthetic Apert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 46 publications
1
14
0
Order By: Relevance
“…Thermal expansion of the infrastructures can be observed in the InSAR results, which have been reported by many previous studies [17][18][19][20]23,26]. For example, this phenomenon was noticed in displacements of the Rainbow Bridge and Lupu Bridge in Tianjin, as well as a highway bridge in Hebei, China [18][19][20].…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Thermal expansion of the infrastructures can be observed in the InSAR results, which have been reported by many previous studies [17][18][19][20]23,26]. For example, this phenomenon was noticed in displacements of the Rainbow Bridge and Lupu Bridge in Tianjin, as well as a highway bridge in Hebei, China [18][19][20].…”
Section: Introductionsupporting
confidence: 59%
“…In the field of infrastructure monitoring, the spaceborne InSAR technique has been gaining more and more popularity [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]; it has been reported to be applicable and effective in monitoring bridges more than once. For instance, Sousa and Basto reported that a deformation rate of about 20 mm/year had occurred before the collapse of a bridge in Italy, demonstrating the potential of MT-InSAR techniques for deformation detection in bridges [12].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to several areas around the world [2][3][4][5][6][7][8][9][10][11], the NCP has experienced rapid land subsidence in association with extensive groundwater withdrawal. Moreover, rapid urbanization, increased dynamic and static loads, and the development of underground spaces have also impacted the occurrence of land subsidence to various degrees [12][13][14][15], and these factors also contribute to land subsidence in the NCP [16][17][18][19][20]. Land subsidence threatens the safety of urban infrastructure, increases the risk of urban waterlogging, exacerbates the impacts of sea-level rise on coastal areas, and even affects regional water security.…”
Section: Introductionmentioning
confidence: 99%
“…This powerful InSAR processing tool implemented in MATLAB, provides a flexible environment for the user to have full control of any technical aspect of PSI analysis. The software was successfully used by several research groups for linear and non-linear deformation monitoring in different applications, such as land subsidence (Fryksten and Nilfouroushan, 2019;Cando Jácome et al, 2020), infrastructures (Bakon et al, 2014;Lyu et al, 2020)…”
Section: Methodology and Data Collectionmentioning
confidence: 99%